Lack of Diagnostic Pluripotentiality in Patients at Clinical High Risk for Psychosis: Specificity of Comorbidity Persistence and Search for Pluripotential Subgroups. (28th September 2017) - Woods, Scott W; Powers, Albert R; Taylor, Jerome H; Davidson, Charlie A; Johannesen, Jason K; Addington, Jean; Perkins, Diana O; Bearden, Carrie E; Cadenhead, Kristin S; Cannon, Tyrone D; Cornblatt, Barbara A; Seidman, Larry J; et al.
Abstract: More than 20 years after the clinical high risk syndrome for psychosis (CHR) was first articulated, it remains controversial whether the CHR syndrome predicts onset of psychosis with diagnostic specificity or predicts pluripotential diagnostic outcomes. Recently, analyses of observational studies, however, have suggested that the CHR syndrome is not pluripotential for emergent diagnostic outcomes. The present report conducted additional analyses in previously reported samples to determine (1) whether comorbid disorders were more likely to persist in CHR patients compared to a comparison group of patients who responded to CHR recruitment efforts but did not meet criteria, termed help-seeking comparison subjects (HSC); and (2) whether clinically defined pluripotential CHR subgroups could be identified. All data were derived from 2 multisite studies in which DSM-IV structured diagnostic interviews were conducted at baseline and at 6-month intervals. Across samples we observed persistence of any nonpsychotic disorder in 80/147 CHR cases (54.4%) and in 48/84 HSC cases (57.1%, n.s.). Findings with persistence of anxiety, depressive, and bipolar disorders considered separately were similar. Efforts to discover pluripotential CHR subgroups were unsuccessful. These findings add additional support to the view that the CHR syndrome is not pluripotential for predicting various diagnostic outcomes but rather is specific for predicting emergent psychosis.